REPRESENTATION OF MULTICULTURAL VALUES IN THE NOVEL LELAKI HARIMAU BY EKA KURNIAWAN - Ramadila, Neyskia; Dzarna, Dzarna; Citraningrum, Dina Merdeka (Universitas Islam Sumatera Utara (UISU), 2025)
Multiculturalism refers to the diversity of life across the world or a cultural framework that emphasizes the acceptance and coexistence of different cultures. Multicultural values, therefore, represent society’s appreciation of all that is considered good, important, noble, appropriate, and functionally beneficial for fostering collective development and the well-being of social life. This study aims to describe the representation of multicultural values in the novel Lelaki Harimau by Eka Kurniawan. The type of research conducted is qualitative; utilizing descriptive analysis methods, while the method employed in this study is content analysis. Based on the study's results, the novel Lelaki Harimau by Eka Kurniawan features 78 quotes that represent multicultural values. The essence of human life has 20 quotes, the essence of human work has 13 quotes, the essence of human position in space and time has 19 quotes, the essence of human relations with nature has 11 quotes, and the essence of human relations with others has 15 quotes. Based on the research results, the representation of multiculturalism values in the form of the essence of human life dominates in this novel, while the multiculturalism values in the form of the essence of human relations with nature are the least. The findings of this study can provide readers with information that the novel Lelaki Harimau by Eka Kurniawan explores individual abilities in living life. Additionally, it can be a reference for readers regarding real-life situations.